Analisis Tingkat Kepuasan Masyarakat Desa Tanjung Menang Kecamatan Rambang Niru Terhadap Pengguna Aplikasi BRI Mobile - Agung, Ahmad Syuri; Fajriyah, Fajriyah; Suhartini, Suhartini (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
In today's information technology era, the world of digital information technology has proliferated, so the use of information technology has undoubtedly increased. This study uses the PIECES method to analyze user satisfaction with the Bri Mobile application. The problems users are still experiencing include many issues, such as complaining about the inability to log in, having difficulty accessing several available menus, often experiencing errors, and being unable to make transactions. Hence, these problems make users less likely to use the Bri Mobile application. The PIECES method measures user satisfaction with the BRI Mobile application using 6 variables: performance, information, economy, control and security, efficiency, and service. the results of the validity and reliability tests are declared valid if they are greater than the r table, which is 0.133. Based on the Likert scale calculation results on all variables, an average of 99.1%.